A Predictive of Loneliness in Sports Sciences Students: Self-Efficacy - M. Sibel yaman, (Pakistan Journal of Medical & Health Sciences, 2022)
In this study, it is aimed to examine the predictive power of self-efficacy on loneliness in sports science students. A total of 255 sports science students, 72 female and 183 male, studying in the Coaching Education and Physical Education and Sports Teaching departments of a state university's Faculty of Sports Sciences, participated in the study, which is carried out using the correlational survey model. In the study, data are collected using the "Personal Information Form", "UCLA Loneliness Scale (ULS-8)" and "General Self-Efficacy Scale". Data are analyzed using descriptive statistics, Pearson correlation and Regression technique. When the research findings are examined, it is determined that there is a negative and low-level significant relationship between loneliness and self-efficacy (p<.05). In addition, it is determined that self-efficacy had a negative predictive power on loneliness (p<.05). As a result, the increase in the self-efficacy of sports science students can make them less lonely.